Knowledge of Human Immunodeficiency Virus Status and Seropositivity After a Recently Negative Test in Malawi. (15th December 2016) - Pathmanathan, Ishani; Lederer, Philip; Shiraishi, Ray W.; Wadonda-Kabondo, Nellie; Date, Anand; Matatiyo, Blackson; Dokubo, E. Kainne
Abstract: Background: Awareness of human immunodeficiency virus (HIV) status among all people with HIV is critical for epidemic control. We aimed to assess accurate knowledge of HIV status, defined as concordance with serosurvey test results from the 2010 Malawi Demographic Health Survey (MDHS), and to identify risk factors for seropositivity among adults (aged 15–49) reporting a most recently negative test within 12 months. Methods: Data were analyzed from the 2010 MDHS. A logistic regression model was constructed to determine factors independently associated with HIV seropositivity after a recently negative test. All analyses controlled for the survey's complex design. Results: A total of 11 649 adults tested for HIV during this MDHS reported ever being sexually active. Among these, HIV seroprevalence was 12.0%, but only 61.7% had accurate knowledge of their status. Forty percent (40.3%; 95% confidence interval [CI], 36.8–43.8) of seropositive respondents reported a most recently negative test. Of those reporting that this negative test was within 12 months (n = 3630), seroprevalence was 7.2% for women (95% CI, 5.7–9.2), 5.2% for men (95% CI, 3.9–6.9), higher in the South, and higher in rural areas for men. Women with higher education and men in the richest quintile were at higher risk. More than 1 lifetime union was significantly associated with recent HIV infection, whereas never being married was significantly protective. Conclusions: Self-reported HIV status based on prior test results can underestimate seroprevalence. These results highlight the need for posttest risk assessment and support for people who test negative for HIV and repeat testing in people at high risk for HIV infection.